2021
DOI: 10.18326/infsl3.v15i1.1-24
|View full text |Cite
|
Sign up to set email alerts
|

Productive Waqf, Economic Empowerment, and Public Welfare: Evidence from Benefit Recipients at Daarut Tauhiid Waqf Institution

Abstract: This study aimed to determine the effect of productive waqf management on public welfare with economic empowerment as an intervening variable. The research method used quantitative research, and the data collection used a closed-ended questionnaire. The sampling was selected based on the purposive sampling technique by determining certain criteria and objectives. The data analysis technique used Partial Least Square (PLS) with the PLS 3 smart application. The results of this study concluded that productive waq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…From the several definitions of waqf, it can be concluded that waqf aims to provide benefits or benefits of the waqf property to people who are entitled and used in accordance with Islamic sharia teachings which is in line and proven that waqf if properly managed has a beneficial development impact (Munawar & Mufraini, 2021). This is in accordance with the waqf function mentioned in article 5 of Law no.…”
Section: Literature Review Waqfmentioning
confidence: 54%
“…From the several definitions of waqf, it can be concluded that waqf aims to provide benefits or benefits of the waqf property to people who are entitled and used in accordance with Islamic sharia teachings which is in line and proven that waqf if properly managed has a beneficial development impact (Munawar & Mufraini, 2021). This is in accordance with the waqf function mentioned in article 5 of Law no.…”
Section: Literature Review Waqfmentioning
confidence: 54%
“…It is a transformative process that enhances wellbeing, community development, self-sufficiency, and expands individual capacities for self-reliance (Olabisi, 2015). Women's economic empowerment, in particular, has been linked to improvements in institutions, finance, and business development (Munawar & Mufraini, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The better the management of productive waqf carried out by the waqf institution, the more indirectly it would improve the public welfare with good economic empowerment. The good of productive waqf management can be used as a benchmark for waqf institutions in managing waqf (Munawar & Mufraini, 2021).…”
Section: Introductionmentioning
confidence: 99%